Optimization theory and practice - Forst, Wilhelm; Hoffmann, Dieter (Springer undergraduate texts in mathematics and technology, 2010)
Optimization---Theory and Practice offers a modern and well-balanced presentation of various optimization techniques and their applications. The book's clear structure, sound theoretical basics complemented by insightful illustrations and instructive examples, makes it an ideal introductory textbook and provides the reader with a comprehensive foundation in one of the most fascinating and useful branches of mathematics.